What Is the Association Between Articular Cartilage Damage and Subsequent THA 20 Years After Hip Arthroscopy for Labral Tears? - Dwyer, Maureen K. (Clin Orthop Relat Res, 2019)
BACKGROUND: Few studies have examined long-term outcomes for patients after arthroscopic treatment for intraarticular hip conditions, and none have done so beyond 10 years postarthroscopy. Examining outcomes beyond 10 years is necessary to determine factors that contribute to conversion to THA in patients undergoing hip arthroscopy for labrochondral damage. QUESTIONS/PURPOSES: (1) What is hip survivorship free from THA in patients who underwent arthroscopic labral débridement, with or without chondroplasty at least 15 years before? (2) What factors are associated with conversion to THA after arthroscopic labral débridement, with or without chondroplasty? (3) Can these data be used to estimate the risk of conversion to THA based on patient- and hip-related factors? METHODS: Between 1989 and 2000, one surgeon performed 552 arthroscopic hip procedures for symptomatic labral tears, with or without associated articular cartilage damage. Of these, the hip status was known in 404 hips (73%) at a minimum of 15 years after the index procedure, with 20 of those patients having died during the followup period. During the study period, patients were offered hip arthroscopy for labral tears with mechanical symptoms, with or without underlying articular cartilage damage. Patient age, sex, acetabular and femoral head Outerbridge grade at surgery, and presence of labral tear were recorded. We determined survivorship free from THA using a Kaplan-Meier survivorship estimator. A stepwise multivariable logistic regression analysis was conducted to determine factors associated with the eventual conversion to THA after hip arthroscopy for labrochondral injuries. Odds ratios (OR) and 95% confidence intervals (95% CI) were calculated for all significant independent factors. Odds ratios for combinations of significant factors were used to create a risk assessment. RESULTS: The survivorship free from conversion to THA at 20 years was 59% (95% CI, 53–64. Factors that affected survival included age ≥ 40 years and the presence of combined femoral head and acetabular chondral damage. After controlling for confounding factors, we found that age ≥ 40 years (OR, 2.0; 95% CI, 1.2–3.4; p = 0.011), the absence of all chondral damage (OR, 0.1; 95% CI, 0.03–0.32; p < 0.001), the presence of acetabular damage with severe femoral head damage (OR, 5.0; 95% CI, 2.4–10.3; p < 0.001), and the presence of severe acetabular damage with femoral head damage (OR, 3.7; 95% CI, 2.0–6.8; p < 0.001) were associated with conversion to THA at long-term followup. Based on the calculated ORs, the probability of conversion to THA by 20 years postarthroscopic treatment for labrochondral injuries ranged from 12% (95% CI, 8–17) for a patient younger than 40 years with a Grade 0-II femoral and acetabular Outerbridge grade to 92% (95% CI, 86–95) for a patient older than 40 years with a Grade III-IV femoral and acetabular Outerbridge grade. CONCLUSIONS: Our study revealed that survivorship free from THA at 20 years after arthroscopic labral débridement was associated with both patient age at time of index procedure and, more importantly, the presence of combined femoral head and acetabular chondral damage. Patients should be counseled as to the increased probability of conversion to THA, depending on the health of their articular cartilage after surgery. Future studies should examine survivorship free from THA or clinical symptoms in patients undergoing hip arthroscopy with bone reshaping procedures or with labral repair or reconstruction up to and exceeding 20 years. LEVEL OF EVIDENCE: Level III, therapeutic study.